2022
DOI: 10.3390/gels8110704
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition of Tonka Bean (Dipteryx odorata) and Its Application as an Elder-Friendly Food with Gelling Agent

Abstract: (1) Background: The purpose of this study was to compare the nutritional characteristics of Tonka beans according to the cooking method and to prove the feasibility of application as an elder-friendly food. (2) Methods: After analyzing the nutritive components, antioxidant activity, and anti-diabetic activity of raw, boiled, and roasted Tonka beans, custards, to which roasted Tonka beans were added, were prepared using a gelling agent to meet the KS viscosity standards (≤1500 mPa.s). (3) Results: The cooking m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Indeed, the coumarin-rich oil from D. odorata seed displayed meaningful antioxidant activity in several in vitro free radical scavenging assays but also had a substantial total phenolic content [196]. Naturally Occurring Antioxidants in Seven Well-Known Fruits from the Republic of Suriname… DOI: http://dx.doi.org /10.5772/intechopen.110078 And raw, roasted, and boiled D. odorata seeds had a considerable coumarin, total phenolic, and total flavonoid contents and displayed meaningful free radical scavenging activity, superoxide dismutase activity, as well as ferric reducing antioxidant power [197]. However, both coumarins and flavonoids in D. odorata seed preparations elicited antioxidant activities [180,184,185] and can be classified as phenylpropanoidderived natural products.…”
Section: Antioxidant Phenolic Compounds: Coumarins: Dipteryx Odorata ...mentioning
confidence: 99%
“…Indeed, the coumarin-rich oil from D. odorata seed displayed meaningful antioxidant activity in several in vitro free radical scavenging assays but also had a substantial total phenolic content [196]. Naturally Occurring Antioxidants in Seven Well-Known Fruits from the Republic of Suriname… DOI: http://dx.doi.org /10.5772/intechopen.110078 And raw, roasted, and boiled D. odorata seeds had a considerable coumarin, total phenolic, and total flavonoid contents and displayed meaningful free radical scavenging activity, superoxide dismutase activity, as well as ferric reducing antioxidant power [197]. However, both coumarins and flavonoids in D. odorata seed preparations elicited antioxidant activities [180,184,185] and can be classified as phenylpropanoidderived natural products.…”
Section: Antioxidant Phenolic Compounds: Coumarins: Dipteryx Odorata ...mentioning
confidence: 99%
“…The modifications also enhance their effectiveness as emulsifiers and stabilizers, particularly in the case of E1450 preparation. In searching for new raw materials for food gels, Kim and Iida [6] compared the nutritional characteristics of Tonka beans obtained by different cooking methods and explored their potential as elder-friendly food. Different cooking methods, such as boiling and roasting, are compared, and it is found that roasted Tonka beans have minor nutrient losses and are suitable for elder-friendly food applications.…”
mentioning
confidence: 99%